A 1 year follow-up of a molar root canal treatment using periapical radiographs and CBCT - Sinziana Adina Scarlatescu; Irina Gheorghiu; Alexandru Andrei Iliescu; Paula Perlea; Bogdan Pricop; Anna Maria Pangica; Stefan Manea (Amaltea Medical Publishing House, 2023)
CBCT offers many significant advantages in dentistry, while the periapical radiographs provide a cheaper technique and a lower radiation compared to CT scan. The aim of this clinical case was to compare the outcome 1 year after root canal treatment, using digital periapical radiographs versus CBCT. Tooth 46 with necrotic pulp and periapical periodontitis was rotary prepared and filled using continuous wave condensation and AH Plus. X-rays and CBCT scans were made both before and after the treatment, at 1 year recall. On x-ray the lesion appeared to be healed, while on CBCT one can still see a smaller lesion, so the tooth is healing. The increased accuracy of CBCT offers the most relevant information for the outcome of endodontic treatment.